The encyclopaedic companion to medical statistics - Everitt, Brian; Palmer, Christopher Ralph (John Wiley & Sons, 2010)
"The Encyclopaedic Companion to Medical Statistics, contains a readable accounts of almost 400 statistical topics central to current medical research. Each entry has been written by an individual chosen for both their expertise in the field and their ability to communicate statistical concepts successfully to medical researchers. Real examples from the biomedical literature and relevant illustrations feature in many entries, and extensive cross--referencing signposts the reader to related entries"--Provided by publisher